2020
DOI: 10.1111/asj.13376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding early‐harvested orchardgrass–perennial ryegrass mixed silage instead of heading stage harvested timothy silage on digestion and milk production in dairy cows

Abstract: High-quality forages are essential diets for high-yielding dairy cows. Grass silage is the main dietary source for dairy cow in Japan. In northern regions of Japan, mainly timothy (Phleum pratense L.) is cultivated as the material for grass silage to optimize the dry matter (DM) yield. However, timothy is less competitive than other grass species, and the DM yield and forage quality are thus reduced due to invasion of rhizomatous grass weeds such as quackgrass and reed canarygrass to the timothy-based grasslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…After the hybrid B. papyrifera feed is fermented, it can increase the effective degradation rate of dry matter and the utilization of nutrients, leading to an increase in milk production ( 34 ). Hybrid B. papyrifera fermented feed increases the peak milk production and slows down the decline in milk production, which can bring more benefits to the farm.…”
Section: Discussionmentioning
confidence: 99%
“…After the hybrid B. papyrifera feed is fermented, it can increase the effective degradation rate of dry matter and the utilization of nutrients, leading to an increase in milk production ( 34 ). Hybrid B. papyrifera fermented feed increases the peak milk production and slows down the decline in milk production, which can bring more benefits to the farm.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix in the extract for sugar analysis of ruminant feeds is varied because various materials such as forage, silage, grains, byproducts from the food industry, and their mixtures are used. In ruminant feeds, fermented feeds such as silage contain lactic acid and acetic acid (Chen et al, 2020;Miyaji et al, 2020). Fujikawa et al (1974) reported that some organic acids (e.g., lactic acid) can give color in the PSA assay.…”
Section: Introductionmentioning
confidence: 99%